Peru : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Peru. (IMF Staff Country Reports; Country Report ;, 2018)
Peru has been one of the top performers in Latin America since the turn of the century: robust growth has helped close the income gap with the largest regional economies and reduce poverty significantly. Last year, however, growth was subpar and the poverty ratio increased. While high commodity prices are an important tailwind, the economy is facing domestic headwinds. The Odebrecht case led to the resignation of President Kuczynski, and the new cabinet has moved quickly to implement various measures and request special legislative powers from Congress. The authorities have also been facing the challenge of rebuilding infrastructure following the extreme weather caused by El Nino in 2017.